Agony of the laborers and daily wagers during the COVID-19 induced lockdown in India: Agony of the poor during the COVID-19 induced lockdown in India - Mukhra, Richa; Krishan, Kewal; Kanchan, Tanuj (Acta Biomedica Atenei Parmensis, 2020)
The COVID-19 pandemic has not only brought the global health crisis but it also triggered the distressing effects on the social and economic life of the people. This pandemic has affected all segments of the population but the most vulnerable sections and occupations are suffering a lot. The communication traces the stipulation and misery of the labourers and daily wagers in India during lockdown, which was implemented as a necessary preventive measure to contain the COVID-19 outbreak.